Geography, Institutions and Regional Economic Performance - Crescenzi, Riccardo; Percoco, Marco; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book brings together contributions by scholars from several countries and different (3z(Bsister(3y (Bdisciplines (Economic Geography, Urban and Regional Economics, Innovation Studies) with different approaches to the same crucial issue: how geography, culture and institutions influence regional economic performance. It includes a number of relevant insights into these complex relations covering different-though complementary-streams of literature in order to emphasize their points of contact and areas of consensus (or disagreement). The role of institutional and cultural factors in shaping regional economic dynamics is analysed together with the impact of clusters, accessibility, urbanization processes and localised inter-firm linkages. The dynamic interactions of economic agents across space are also explored in depth by analysing the geography of trade flows, labour and capital mobility. Empirical analyses cover the whole European Union with some chapters focused on specific European countries but also on non-European and emerging economies. The book effectively demonstrates that regional development is a complex and multifaceted phenomenon, the in-depth understanding of which calls for the simultaneous consideration of a variety of phenomena and the structural characteristics of places and agents. The understanding of regional economic performance hence calls for an explicit consideration of both (3z(Bhard(3y (Band (3z(Bsoft (3y (Bfactors of development, especially in terms of geography, culture and institutions.s
Space, Growth and Development -- Institutions and Culture -- Agglomeration Economies, the Location of Economic Activities and Innovation -- Geography in Motion: Trade, FDI and Migrations.
Keywords: Economics; Geography; Europe -- Economic policy; Regional economics; Economics/Management Science; Regional/Spatial Science; R & D/Technology Policy; European Integration; Economic Geography